Nonlinear dynamic model and simulation of morphing wing profile actuated by shape memory alloys - Faria, Cassio T.; De Marqui Jr., Carlos; Inman, Daniel J.; Lopes Jr., Vicente [UNESP] (Springer Nature, 2012)
Morphing aircraft have the ability to actively adapt and change their shape to achieve different missions efficiently. The development of morphing structures is deeply related with the ability to model precisely different designs in order to evaluate its characteristics. This paper addresses the dynamic modeling of a sectioned wing profile (morphing airfoil) connected by rotational joints (hinges). In this proposal, a pair of shape memory alloy (SMA) wires are connected to subsequent sections providing torque by reducing its length (changing airfoil camber). The dynamic model of the structure is presented for one pair of sections considering the system with one degree of freedom. The motion equations are solved using numerical techniques due the nonlinearities of the model. The numerical results are compared with experimental data and a discussion of how good this approach captures the physical phenomena associated with this problem. © The Society for Experimental Mechanics, Inc. 2012.
Keywords: Morphing wing; Nonlinear dynamics; Shape memory alloy; Degree of freedom; Dynamic modeling; Experimental data; Morphing; Morphing aircrafts; Morphing structures; Morphing wings; Numerical results; Numerical techniques; Physical phenomena; Rotational joint; Shape memory alloy wire; Wing profiles; Airfoils; Dynamics; Equations of motion; Structural dynamics; Shape memory effect